Early Oral Rehydration Therapy in Diabetic Ketoacidosis: A Randomized Controlled Study - Kola, Shourya Vijay Tej; Gupta, Shalu; Kumar, Virendra (Journal of Pediatric Intensive Care, 2022)
Objectives We aimed to compare the efficacy of oral versus intravenous (IV) fluid therapy in correcting dehydration in diabetic ketoacidosis (DKA) when pH was ≥ 7.25 and Glasgow coma scale (GCS) score was ≥12. We also compared the time to resolution of DKA.Subjects Children aged ≤18 years with DKA were included in the study. In our pilot study, 40 children were enrolled from June 2018 to April 2019 and divided into two groups after achieving pH ≥ 7.25 and GCS score ≥ 12.Materials and Methods This was an open-label, parallel-arm, randomized control trial conducted in the pediatric intensive care unit of a tertiary referral hospital in North India. The IV group (control group) received treatment as per the standard protocol, whereas the oral group (trial group) received only oral fluids; IV fluid was withheld for 48 hours. Dehydration was clinically assessed on admission and after 48 hours, and the proportion of children achieving correction of dehydration was compared. Biochemical parameters were measured over time, and the time taken for resolution was compared between groups.Results Both groups achieved successful correction of dehydration. No significant difference was observed in the time taken from randomization to complete resolution of DKA. Hyperchloremia improved significantly earlier in the oral group after randomization.Conclusion Early institution of oral rehydration strategy after achieving pH ≥ 7.25 and GCS score ≥ 12 was effective in correcting dehydration at a rate comparable to standard IV rehydration. Hyperchloremia was observed to resolve earlier in patients that received oral rehydration therapy.
Keywords: diabetic ketoacidosis; oral rehydration therapy; fluid therapy; intravenous fluid; dehydration